A low-cost wireless sensors positioning solution for indoor parking facilities management. (1st October 2016) - Gikas, Vassilis; Antoniou, Constantinos; Retscher, Guenther; Panagopoulos, Athanasios; Kealy, Allison; Perakis, Harris; Mpimis, Thanassis
Abstract: A relatively low-cost system for indoor parking facilities management is proposed, which is a combined solution of RFID/WiFi and a MEMS IMU monitoring scheme. An RFID localisation module is proposed in the form of so-called virtual gates. To define such virtual gates, either RFID tags or readers are placed at known locations throughout the area of interest. In this study, a number of tags are fixed at known positions and a moving reader is carried by each participating vehicle. Based on this configuration set-up, the Cell of Origin (CoO) technique is applied, in which the system indicates the presence of the user carrying the reader in a cell around the tag location. To define a virtual gate, tags are installed along the parking lot corridors and at critical transit passages in the parking facility. The CoO technique is also proposed in the case of WiFi for location determination of vehicles in a multi-storey car park. In this study, WiFi is employed to monitor the passing vehicles and bridge the gap until a tag can detect a user's reader again. Thus, a combined positioning solution of RFID and WiFi is achieved. As a complement to the proposed RFID/WiFi system, this study examines the potential and limitations of MEMS IMU sensors (i.e. accelerometers, gyroscopes and barometers) commonly found in modern smartphones. The paper concludes with a detailed discussion on the implications of alternative positioning techniques for indoor parking management.